DESCRIBING THE EFFECTIVENESS OF USING YOUTUBE MEDIA TO IMPROVE STUDENTS' LEARNING SKILLS IN CONGREGATIONAL PRAYER TEACHING MATERIALS - Safuroh, Safuroh; Supandi, Supandi; Hidayatullah, Hidayatullah (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2024)
The importance of learning media during learning is very influential in the delivery of teaching material and achievement of learning objectives to students. The aim of this research is to analyze the skills possessed by students before treatment using YouTube media in congregational prayer teaching materials, student learning outcomes after treatment using YouTube media in congregational prayer teaching materials, and the effectiveness of using YouTube media in improving learning outcomes. This observation method, namely the research design, is a pre-experimental design. The observation design uses a single group pre-test and post test design. The sample used in this observation was a purposive sampling technique. We will clearly know the effectiveness of using YouTube media supported by educational videos as a learning medium for congregational prayer teaching materials with the following four Normalized Gain test analyzes: High ranking percentage is 22,72 percent, medium category percentage is 72,72 percent, low category percentage of 9,09 percent, the constant category percentage was 4,54 percent, and the decreasing category percentage was 4,54 percent. Based on the research results 9,09% of students who were not yet proficient passed the skills test, 90,90% passed, the average skill level of all students was 87,95 points, and the learning completion rate was 90,90%. So YouTube media can effectively improve learning skills in congregational prayer teaching materials. The use of YouTube media can be applied in Madrasas, because it has been proven to improve learning outcomes.